2012
DOI: 10.3319/tao.2011.10.06.02(oc)
|View full text |Cite
|
Sign up to set email alerts
|

SGOTL: A Computer Program for Modeling High-Resolution, Height-Dependent Gravity Effect of Ocean Tide Loading

Abstract: SGOTL, a computer package coded in FORTRAN, has been developed to model the gravity effect due to ocean tide loading (OTL), especially for a coastal station with large ocean tides. SGOTL uses a regional and a global tide model to account separately for near (inner) and far (outer) zone contributions, and optimizes an inner-zone region and grid interval for numerical convolution. Height dependent Green's functions for Newtonian and elastic effects are developed. The coastline is defined by the full-resolution G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The improved accuracies are most pronounced at the sites with elevations > 1000 m, suggesting that the altitude of a gravity site should be considered when computing the OTL effect. This conclusion is consistent with that made in Hwang and Huang (2012).…”
Section: Adjustments Of Relative Gravity Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…The improved accuracies are most pronounced at the sites with elevations > 1000 m, suggesting that the altitude of a gravity site should be considered when computing the OTL effect. This conclusion is consistent with that made in Hwang and Huang (2012).…”
Section: Adjustments Of Relative Gravity Measurementssupporting
confidence: 93%
“…The temporal gravity effects due to solid earth tide in all gravity measurements were removed using the model values of ETGAB (Wenzel, 2002;Dehant et al, 1999). The Newtonian effect and the loading effect of ocean tides (called OTL correction) were removed using the FES2004 tide model (Letellier et al, 2004) and the SGOTL software (Hwang and Huang, 2012), which considers the elevation of a gravity site. We also removed the effects of barometric pressure and polar motions using a SG-based gravity-atmosphere admittance coe cient (see below) and the earth rotation parameters from the International Earth Rotation Service and Reference Systems.…”
Section: Gravity Data Collections and Correctionsmentioning
confidence: 99%
“…It has been suggested that station elevation also affects the calculation results of tidal gravity loading effect (Hwang and Huang, 2012). Some of the stations used in this study have large elevations; CBS and MDJ are at > 1000 m. If a uniform elevation is used to calculate tidal loading, the accuracy of the calculation results will have an error of ~1.7× 10 −8 ms −2 .…”
Section: Ocean Tide Modelsmentioning
confidence: 95%
“…The observed gravity changes in April, July, September, and November 2012. The stations Y20 (Chishinshan), YMSG (Chintiengang), Y08 (Dayoukeng), and Y03, at the different geological backgrounds, are denoted Lien et al Terrestrial, Atmospheric and Oceanic Sciences (2022) 33:31 2004) and the SGOTL software (Hwang and Huang 2012), which takes the elevation of the gravity site into account. The OTL correction preformed using SGOTL improved the point gravity accuracies in the adjustments by 1.4% to 6.2% compared to the cases where OTL correction was not applied.…”
Section: Figmentioning
confidence: 99%